Quantifying barriers to movement of service suppliers and examining their effects: Implications for COVID-19 - Anirudh Shingal (Indian Council for Research on International Economic Relations (ICRIER), 2020)
The importance of services trade and "servicification" of economic activity has grown in countries overtime. However, regulatory and administrative barriers to the movement of service suppliers have meant that "Mode 4" accounted for only 2.1% of total services trade in 2005 and 2.9% in 2017. While trade costs for services have been computed in the literature, barriers specific to Mode 4 services trade have not yet been quantified. We contribute by constructing an index to quantify regulatory barriers to the movement of service suppliers, using qualitative information embedded in OECD data on services trade restrictions, and examining its relationship with services trade by "mode" of supply. Results show that the Mode 4 restrictiveness index is negatively correlated with services imports in three of the four modes of services delivery that require proximity between buyers and sellers. Notably, services delivered by these modes are already adversely affected by COVID-19. These findings thus further underline the need for countries to refrain from imposing prohibitive restrictions on service suppliers during this pandemic.
Keywords: F1; F10; F13; 330; Services trade; Mode 4; services suppliers; STRI; COVID-19